Priority-Setting for Children’s Mental Health: Clinical Usefulness and Validity of the Priority Criteria Score - Cawthorpe, David (Canadian Academy of Child and Adolescent Psychiatry, 2007)
OBJECTIVE: The 17-item PCS was designed for priority-setting and queue management of children and adolescents referred for mental health services. Here we assess aspects of the validity of the Children’s Mental Health (CMH) Priority Criteria Score (PCS), developed by the Western Canada Waiting List Project (WCWL). The PCS was evaluated across clinical settings of increasing acuity and in terms of its relationship to two variables reflecting criteria-related validity and actual wait times. METHOD: Intake workers completed PCS forms for 497 referrals enrolled for treatment in three clinical areas over approximately two fiscal years. The completion time of the PCS form was estimated in relation to the total referral and screening process. Intake workers completed the PCS items and did not use the total score at the time of intake and form completion to triage or place clients; hence, the PCS was independent of enrollment and placement within the continuum of care. Furthermore, clinicians in the receiving programs had to accept the triage decisions for the PCS to be used in the study analysis. RESULTS: The PCS score was meaningfully related to the measures of criteria-related validity (e.g., clinician perceived urgency, clinician perceived maximum acceptable waiting times) and triage to clinical settings of increasing acuity. There was a significant mean difference in the PCS for those accepted to community, day, or inpatient settings. CONCLUSIONS: The PCS appears to be a useful, efficient measure of clinical urgency adequate for use in priority-setting for children waiting for mental health services.